Transformation and African migrants: The conflicting worlds of cultural beliefs and marriage issues in No longer at ease and Chairman of fools - Smit, Talita Christine; Indongo, J. N (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Human beings can be moulded by the geographical location in which they find themselves. Many Africans, just like Obi in No longer at ease and Farai in Chairman of fools, travel overseas for education and better paid jobs. During vacations or upon completion of their studies most of these Africans return home to their families in Africa. Some of them encounter conflicts because they expect the people who remained in Africa to behave in the same way as they behaved in the past. The returnees do not consider that even they themselves have changed and life is not stagnant. Paradoxically, the migrants also seem to expect African societies to operate in exactly the same way as those societies they have been immersed in while overseas. This article presents an investigation of the way African authors depict characters migrating between two continents and how these characters are affected by the conflicting geographical, as well as metaphysical, worlds they live in. In the two novels studied it appears that the differences in cultural beliefs and marriage issues are responsible for the inner and interpersonal conflicts that the main characters experience